Development and Validation of a Long Jump Training Model for Beginner Athletes - Joni Marindra; Junaidi Junaidi; Mansur Jauhari (Sriwijaya University Learning and Education International Journal, 2024)
This study aims to be a reference and example of long jump training in compiling long jump training for beginner athletes. The purpose of this model is to:1. Creating a model of long jump training for novice athletes. 2. Understand the effectiveness of long jump training for beginner athletes. This research also aims to produce products in the form of applications that contain variations or results of long jump training models. Variations of the long jump training model are expected to help athletes in the long jump training process and are used by coaches to be a reference in long jump training for beginners. This study applied 12 long jump training models for leading athletes as many as 30 athletes as experimental subjects who were given treatment using variations of long jump training models. The method approach used in this research is the development research method. Research on the development of this physical fitness exercise model uses the development model (Research and Development) from ADDIE. Based on the data that has been obtained, the figures in the table above can be concluded that the long jump training model for beginner athletes can and is feasible to be used in physical fitness training. There is a comparison of numbers that shows that the results  of the initial test average = 120.2 and the final test = 123.36 with the treatment of the long jump model have increased significantly. So it can be concluded that the long jump training model for beginner athletes is effective to be used in fitness training.